Organic Nitrate Therapy, Nitrate Tolerance, and Nitrate-Induced Endothelial Dysfunction: Emphasis on Redox Biology and Oxidative Stress - Daiber, Andreas (Antioxid Redox Signal, 2015)
Organic nitrates, such as nitroglycerin (GTN), isosorbide-5-mononitrate and isosorbide dinitrate, and pentaerithrityl tetranitrate (PETN), when given acutely, have potent vasodilator effects improving symptoms in patients with acute and chronic congestive heart failure, stable coronary artery disease, acute coronary syndromes, or arterial hypertension. The mechanisms underlying vasodilation include the release of (•)NO or a related compound in response to intracellular bioactivation (for GTN, the mitochondrial aldehyde dehydrogenase [ALDH-2]) and activation of the enzyme, soluble guanylyl cyclase. Increasing cyclic guanosine-3′,-5′-monophosphate (cGMP) levels lead to an activation of the cGMP-dependent kinase I, thereby causing the relaxation of the vascular smooth muscle by decreasing intracellular calcium concentrations. The hemodynamic and anti-ischemic effects of organic nitrates are rapidly lost upon long-term (low-dose) administration due to the rapid development of tolerance and endothelial dysfunction, which is in most cases linked to increased intracellular oxidative stress. Enzymatic sources of reactive oxygen species under nitrate therapy include mitochondria, NADPH oxidases, and an uncoupled (•)NO synthase. Acute high-dose challenges with organic nitrates cause a similar loss of potency (tachyphylaxis), but with distinct pathomechanism. The differences among organic nitrates are highlighted regarding their potency to induce oxidative stress and subsequent tolerance and endothelial dysfunction. We also address pleiotropic effects of organic nitrates, for example, their capacity to stimulate antioxidant pathways like those demonstrated for PETN, all of which may prevent adverse effects in response to long-term therapy. Based on these considerations, we will discuss and present some preclinical data on how the nitrate of the future should be designed. Antioxid. Redox Signal. 23, 899–942.